2006
DOI: 10.1093/rpd/ncm165
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of bioassay methods to improve assessment of incorporated radionuclides

Abstract: The present work which was carried out in the framework of an EU project (IDEA: Internal Dosimetry-Enhancements in Application; Contract Number: FIKR CT2001 00164) shall provide commonly acceptable guidelines for optimum performance of ICP-MS measurements with focus on urinary measurements of uranium, thorium and actinides. From the results of this work it is recommended that, whenever feasible, 24 h urine sampling should be conducted to avoid large uncertainties in the quantitation of daily urinary excretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The ICRP uranium model (ICRP, 1995a,b) also predicted such an increase under conditions of a continuous level of intake. In contrast, Hoellriegl et al, (2011) and Oeh et al, (2007) concluded that there was no dependency of uranium excretion with age, which is consistent with our conclusion.…”
Section: Urine Samplessupporting
confidence: 91%
See 2 more Smart Citations
“…The ICRP uranium model (ICRP, 1995a,b) also predicted such an increase under conditions of a continuous level of intake. In contrast, Hoellriegl et al, (2011) and Oeh et al, (2007) concluded that there was no dependency of uranium excretion with age, which is consistent with our conclusion.…”
Section: Urine Samplessupporting
confidence: 91%
“…Much concern has been raised about the exposure of humans to elevated levels of radionuclides from nuclear-related activities such as uranium mining and processing, nuclear fuel production, nuclear waste storage (Blanchard et al, 1982;Gallop et al, 1998), and depleted uranium (Oeh et al, 2007). However, other uranium-bearing mines, such as coal mines, may also cause pollution in nearby environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument parameters and the method applied have been described elsewhere (Roth et al, 2005;Oeh et al, 2007b). Prior to measurement, all the solid food and cigarette samples were digested using extraction with aqua regia according to the German standard method DIN 38414-S7.…”
Section: Icp-ms Measurementsmentioning
confidence: 99%
“…Thorium standards of 1, 2, 5, 10 ng L À1 concentration range were employed to calibrate the instrument. The details regarding instrument parameters, quality control, and optimization are provided elsewhere (Oeh et al, 2007;Roth et al, 2005;Schramel et al, 1999). Using this method, it was possible to achieve a detection limit of 20 pg 232 Th per liter urine.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%